EVALUATING ENVIRONMENTAL HEALTH INVESTIGATIONS: LESSONS FROM THE 2017 LISTERIOSIS OUTBREAK LINKING TO 2024 CHEMICAL FOOD POISONING IN SOUTH AFRICA (Proceedings of the International Conference on Public Health, 2026)
A total of 1060 laboratory-confirmed cases of listeriosis and 216 deaths were reported by National Institute of Communicable Diseases (NICD) in South Africa from January 2017 to July 2018. A ready-to-eat, processed meat product called polony was identified as the source of the outbreak. The World Health Organization (WHO) described this as the largest listeriosis outbreak that had ever been detected worldwide. This study aimed to examine the environmental health investigation methods on Listeriosis outbreak in South Africa during that period. The study identified factors to determine their association with the effectiveness of Listeriosis outbreak investigation. The study was conducted amongst 333 Environmental Health Practitioners (EHPs) at local government, who were directly involved in the outbreak in Gauteng, Western Cape and Kwazulu-Natal as the provinces that recorded the highest number of cases. Quantitative data was collected using a piloted online questionnaire with a set of close-ended and open-ended questions and was analyzed using Statistical Package for the Social Sciences (SPSS) software. The majority of participants, 316 (94.9%) were trained on outbreak investigation. About 298 (94.3%) of these participants trained in outbreak investigation participated in the 2017-2018 Listeriosis outbreak investigation. While participants reported challenges relating to location of cases to impact the effectiveness of outbreak investigation, other factors including improved human resources (50.8%), tools of trade and technology (30%) and legislative and policy framework (19.2%) were recommended for intervention to ensure effective outbreak investigations. These factors were also highlighted in the recent chemical food poisoning reports as areas of concern requiring urgent intervention. This as a result of the reported 22 children dying from chemical food poisoning-related illnesses since the beginning of 2024. Studies have investigated Listeriosis knowledge levels amongst consumers, analysed media messages on the outbreak and provided reviews on outbreak investigation reports and food systems governance in South Africa. This paper provides the perspective of EHPs knowledge and investigative methods during the outbreak and how these approaches link to the chemical food poisoning.
Keywords: Listeriosis; chemical food poisoning; Environmental Health Practitioners; outbreak investigation; listeria monocytogenes; food contamination